Perineal herniorrhaphy along with anal sacculectomy in dog: Case report - Jiregna Dugassa Kitessa; Kisi Bekele Terefe (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
A perineal hernia may occur unilateral or bilateral to the perineum. This may be due to the weakening and disassembly of the pelvic floor muscles, leading to abdominal visceral herniation to the perineal region and needing surgical reconstruction of the pelvic floor. The purpose of this case report is to describe the surgical correction of unilateral perineal hernia along with anal sacculectomy using transposition of internal obturator muscle. After aseptic preparation of the surgical site, an elliptical skin incision over the hernia swelling was performed. From there, the presence of the sac, contents, and adhesion were evaluated, the contents were relocated and the opening was closed with a layer. In the same manner, the anal gland was excised by surgical means. Clinical outcomes including postoperative complications and recur are assessed. Upon regular follow-up, for two months the case didn't recur and suddenly died later for unrelated reasons.